Struktur Kesadaran Tokoh Utama Aletta Arkanza Dalam Novel I’m A Good Girl Karya Zahrani Salsabila (Kajian Psikologi Sastra) (International Forum of Researchers and Lecturers, 2023)
This study aims to: 1) Describe the form of soul function of the character Aletta Arkanza in the novel I'm A Good Girl by Zahrani Salsabila, 2) Describe the form of the attitude of the soul of the character Aletta Arkanza in the Novel I'm A Good Girl by Zahrani Salsabila. This study uses the study of Literary Psychology by utilizing Carl Gustav Jung's theory. This research is a type of qualitative research that is descriptive in nature. The source of this research data is text in the form of words or sentences that indicate the existence of soul functions and mental attitudes of the Aletta Arkanza character, Carl Gustav Jung's theory. Data collection techniques in this study are using library research, reading techniques and note-taking techniques. The data in this study were analyzed using data analysis techniques by identifying, classifying, analyzing, describing, and drawing conclusions. The results of this study indicate that 1) The function of the soul in Aletta Arkanza's character there are four functions of the soul of thought, feeling, intuition and sensing which Jung distinguished into two characteristics, namely rational and irrational. 2) There are two characteristics of the attitude of the soul in the character Aletta Arkanza, namely introvert and extrovert.